The Right to Be Nudged? Rethinking Social and Economic Rights in the Light of Behavioral Economics - Gauri, Varun (World Bank, Washington, DC, 2019)
Social and economic and rights are incorporated into many national constitutions, and courts in many countries are effectively and legitimately enforcing them. However, the large majority of rights rulings addresses the cost of goods and services and focuses exclusively on access. There is now strong evidence that internal, psychological factors limit the enjoyment of social and economic rights, and that nudges and other behavioral insights can increase welfare and support rights fulfillment. These facts suggest there exists a right to be nudged, or at least a duty to use behavioral insights in the provision of social and economic goods and services. The evidence suggests that a shift in choice architecture that shifts the burden of proof to the state in social and economic rights cases, the simplification of procedures for program eligibility and signup, the establishment of agencies to balance private advertising, the promotion of medications adherence, efforts to change student beliefs about learning, and opt-out savings programs are particularly promising.